Feeding biotreated rumen digesta affects nutrient digestion, ruminal fermentation, and blood parameters in calves - Kian Sadeghi; Farhad Parnian-Khajehdizaj; Mahdi Ganjkhanlou; Samad Zamanzad-Ghavidel; Reza Faraji; Valiollah Palangi; Rasoul Kowsar (Scientific Reports)
Abstract The objective of this research was to examine the impact of feeding biologically treated rumen digesta (BTRD) to Holstein steer calves at levels of 0, 10, 20, and 30% (DM-based) on feed consumption, nutrient digestion, growth performance, rumen fermentation, and plasma metabolites. Sixteen Holstein steer calves with an initial BW of 113 ± 8 kg were randomly allocated in a randomized complete design. Dietary inclusion of BTRD in calves diet did not altered (P < 0.05) total intakes of DM, OM, and CP, when compared to those on the control diet over the experiment, but improved (P < 0.01) NDF and ADF consumption. Dietary inclusion of BTRD by 20% increased significantly DM and OM digestibility, average daily gain and feed efficiency (FE) (P < 0.05) and decreased feed conversion ratio (FCR) during 60 to 120 days. Plasma glucose, triglyceride, total protein, creatinine, or urea-N concentrations between treatments were not affected, but uric acid was reduced linearly (P = 0.02) in steers given BTRD supplements. Supplemented diets containing BTRD had the highest levels of plasma cholesterol and HDL, which increased with increasing BTRD inclusion levels. BTRD supplements were found to lower MDA levels in steers than control diets. This study found that dietary BTRD supplementation improved performance and health status of Holstein steer calves as well as their oxidative parameters.